Inhibitory Effects of Lipophilic Acids and Related Compounds on Bacteria and Mammalian Cells - Sheu, C. W. (1975)
The inhibitory effect of lipophilic acids, antimicrobial food additives, and analgesics-antipyretics was examined at concentrations from 0.1 to 100 mM in bacteria (Bacillus subtilis and Escherichia coli) and mammalian cells (HeLa, human fibroblasts, and mouse neuroblastoma cells). Most compounds inhibit the growth of HeLa cells about as efficiently as that of B. subtilis. However, butyrate and propionate, as well as acetaminophen, antipyrene, phenacetin, and salicylamide, inhibit HeLa at millimolar concentrations whereas, at least 10 times higher concentrations are needed to inhibit B. subtilis. The concentrations needed to inhibit growth by 50% decrease with increasing octanol-water partition coefficients of the compound. Growth of E. coli is inhibited similar to that of B. subtilis by all compounds except butylbenzoate, decanoate, and linoleate which cannot penetrate the lipopolysaccharide layer. All growth inhibitors inhibit amino acid uptake into bacteria and their vesicles, and oxygen consumption in bacteria. In HeLa cells or human fibroblasts, neither amino acid uptake nor adenine 5′-triphosphate synthesis are inhibited by fatty acids at concentrations that completely inhibit growth. Short chain fatty acids (propionate, butyrate, and pentanoate) induce in HeLa the formation of cell processes. In neuroblastoma cells, grown in the presence of 10% fetal calf serum, butyrate also induces such processes which slowly continue to grow in length for at least 7 days; these processes differ in speed of formation, width, and cycloheximide susceptibility from the thin processes produced by serum deprivation alone.